The Great Ice battle - Abbott, Tony.; Jessell, Tim (New York : Scholastic, 1999)
Neal and his friends must find a way to save Jaffa City from being frozen because of Lord Sparr's curse.
"A Little Apple paperback."
3.1
3-6
Keywords: Fantasy; Fantasy fiction